Business process re-enginering of tourism e-marketplace by engaging government, small medium enterprises and tourists - Kadek Cahya Dewi; Ni Wayan Dewinta Ayuni (Institute of Advanced Engineering and Science, 2021)
Not all tourism actors in Indonesia had utilize the e-marketplace. Therefore, one of the Indonesian government's focus is to improve the tourism business process model through e-marketplace based system. The research purpose was to re-engineer the business process of tourism e-marketplace by engaging government, small medium enterprises (SMEs) and tourists. The research used the mixed method approach that conducted by modifying The McKinsey BPR methodology. As the result, this research adding two novel aspects to the previous research which are